Re-irradiation new frontiers - Nieder, C. (Carsten) 1964-; Langendijk, Johannes A. (Springer, 2011)
New developments such as refined combined modality approaches and significant technical advances in radiation treatment planning and delivery are facilitating the re-irradiation of previously exposed volumes. As a consequence, both palliative and curative approaches can be pursued at various disease sites. Re-irradiation: New Frontiers is the first book to provide a comprehensive overview on current re-irradiation strategies. Re-irradiation methods, technical aspects, the role of combined therapy with anticancer drugs and hyperthermia, and normal tissue tolerance are all discussed in detail. In addition, disease-specific chapters document recent clinical results and future research directions. Professionals involved in radiation treatment planning and multimodal oncology treatment will find this book to be an invaluable aid in understanding the benefits and limitations of re-irradiation and in designing prospective trials.